Mechanisms and therapeutic opportunities in metabolic aberrations of diabetic wounds: a narrative review - Yuan Xiong; Samuel Knoedler; Michael Alfertshofer; Bong-Sung Kim; Dongsheng Jiang; Guohui Liu; Yuval Rinkevich; Bobin Mi (Cell Death and Disease)
Abstract Metabolic aberrations are fundamental to the complex pathophysiology and challenges associated with diabetic wound healing. These alterations, induced by the diabetic environment, trigger a cascade of events that disrupt the normal wound-healing process. Key factors in this metabolic alternation include chronic hyperglycemia, insulin resistance, and dysregulated lipid and amino acid metabolism. In this review, we summarize the underlying mechanisms driving these metabolic changes in diabetic wounds, while emphasizing the broad implications of these disturbances. Additionally, we discuss therapeutic approaches that target these metabolic anomalies and how their integration with existing wound-healing treatments may yield synergistic effects, offering promising avenues for innovative therapies.